On the smoothness of the Green function for the problem of bounded invariant manifolds - Burilko, O. A.; Samoilenko, A. M. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We investigate the smoothness of the Green function for the problem of bounded invariant manifolds of linear extensions of dynamical systems.